Studi Komparasi Model Kepemimpinan Kepala Negara Ganda dalam Sistem Pemerintahan Diarki di Beberapa Negara - Abidin AS, Zaenal; Iqbal, Firdaus Muhamad (Resolusi: Jurnal Sosial Politik, 2025)
A diarchy, or dual head-of-state leadership system, is a governance model in which two individuals jointly exercise the functions of the head of state. This study analyzes the impacts and challenges of the diarchy system in modern contexts by examining its implementation in several countries, including Andorra, San Marino, and Nicaragua. A qualitative methodology was employed, utilizing secondary data analysis through literature reviews, constitutional documents, and related academic sources. The findings demonstrate that the diarchy system offers improved power balance, enhances governmental legitimacy, and fosters administrative efficiency. However, the system also faces challenges, such as potential leadership conflicts, political fragmentation, and the risk of dominance by one leader, which may undermine principles of equality in governance. Furthermore, the application of diarchy in democratic and authoritarian systems yields varied outcomes, depending on the availability of checks and balances. Therefore, the success of a diarchy system hinges on legal frameworks, political traditions, and institutional capacity to maintain governmental stability.